1996
DOI: 10.1897/1551-5028(1996)015<1470:osafot>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Sources, and Fate of Trichloroacetic Acid in Swiss Waters

Abstract: The occurrence, sources, and fate of trichloroacetic acid (TCA) has been investigated in surface waters, ground waters, drinking waters, wastewaters, and rainwater in Switzerland. The concentrations found in surface waters varied between less than 27 ng/L (limit of quantification) and 340 ng/L, whereas the concentrations in ground water were always below 27 ng/L. It was found that the main sources of TCA in surface waters were the effluents of wastewater treatment plants (average concentration, 430 ng/L; range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Also, citric acid was found to promote chloroform formation. These results are identical with other previous studies by Müller (1996) which demonstrated that TCA could form esters with substances such as dimethoxyphenol, a model for humic acid, which subsequently decompose giving chloroform and other by-products (McCulloch, 2002). However, an apparent promotion for chloroform formation by acetic acid in our experiment was also observed.…”
Section: Table VIIIsupporting
confidence: 93%
See 2 more Smart Citations
“…Also, citric acid was found to promote chloroform formation. These results are identical with other previous studies by Müller (1996) which demonstrated that TCA could form esters with substances such as dimethoxyphenol, a model for humic acid, which subsequently decompose giving chloroform and other by-products (McCulloch, 2002). However, an apparent promotion for chloroform formation by acetic acid in our experiment was also observed.…”
Section: Table VIIIsupporting
confidence: 93%
“…Several investigations of TCA concentrations in lake waters have been published. In 1992/1993 measurement of TCA concentration in Lake Greifensee, Switzerland showed an interesting variation with depth, ranging between 0.06 µg L −1 in the hypoliminion and 0.13 µg L −1 in the epilimnion (Müller et al, 1996). However, studies on the fate of TCA in lake waters have scarcely been published.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The half-life of TCAA in a lake has been calculated by a dynamic mathematical model as greater than 230 d [19]. However, little is known about the stability of haloacetic acids in seawater.…”
Section: Stability Of Haloacetic Acids In the Aquatic Environmentmentioning
confidence: 99%
“…Haloacetic acids have been found in various environments such as rain water [13][14][15][16][17][18][19], river water [9,19,20], and conifer needles [15,16,21,22]. The haloacetic acids released from industrial wastewater, river water, and rain water may accumulate in semienclosed water bodies such as Tokyo Bay, Japan, an area that is highly eutrophic and polluted.…”
Section: Introductionmentioning
confidence: 99%